Intrathyroidal Ectopic Thymus in Children: Retrospective Analysis of Grayscale and Doppler Sonographic Features. (12th August 2015) - Yildiz, Adalet Elcin; Ceyhan, Koray; Sıklar, Zeynep; Bilir, Pelin; Yağmurlu, Emin Aydın; Berberoğlu, Merih; Fitoz, Suat
Abstract : Objectives: The purpose of this study was to define grayscale and color Doppler sonographic features of an ectopic intrathyroidal thymus and to differentiate it from other thyroid nodule etiologies. Methods: We retrospectively reviewed imaging findings from 30 children who had a diagnosis of an ectopic intrathyroidal thymus from November 2005 to January 2013. Nodular thyroid lesions that were enclosed by the thyroid parenchyma and showed a typical echo pattern consistent with the thymus were accepted as the enclosed form of an intrathyroidal ectopic thymus. Eleven of these 30 children had an intrathyroidal ectopic thymus enclosed by the thyroid parenchyma, and they were enrolled in the study. The recorded sonograms were reviewed according to side, location, size, shape, echo pattern, internal content, and vascularization. Results: The enclosed forms of ectopic intrathyroidal thymuses were unilateral in all children and located in the mid portion (n = 10) or lower portion (n = 1). All lesions were well demarcated, and the most common shape was fusiform (n = 8). Nine lesions showed a typical hypoechoic echo pattern with internal linear and punctate echoes resembling a mediastinal thymus. On color Doppler imaging, 6 lesions showed hypovascularity compared to the thyroid parenchyma, and 5 lesions showed internal vascularity. Conclusions: Unique sonographic features of the enclosed form of an ectopic intrathyroidal thymus, including a hypoechoic echo pattern with multiple linear and punctate echoes, a fusiform shape, a well‐demarcated contour, and a mid‐ or low‐lying location with hypovascularity or internal vascularity, can help radiologists differentiate it from other thyroid nodule etiologies.